Managing conflicts between economic activities and threatened migratory marine species toward creating a multiobjective blue economy. Issue 2 (12th January 2018) - Harris, Linda R.; Nel, Ronel; Oosthuizen, Herman; Meÿer, Mike; Kotze, Deon; Anders, Darrell; McCue, Steven; Bachoo, Santosh
Abstract: Harnessing the economic potential of the oceans is key to combating poverty, enhancing food security, and strengthening economies. But the concomitant risk of intensified resource extraction to migratory species is worrying given these species contribute to important ecological processes, often underpin alternative livelihoods, and are mostly already threatened. We thus sought to quantify the potential conflict between key economic activities (5 fisheries and hydrocarbon exploitation) and sea turtle migration corridors in a region with rapid economic development: southern and eastern Africa. We satellite tracked the movement of 20 loggerhead (Caretta caretta) and 14 leatherback ( Dermochelys coriacea ) turtles during their postnesting migrations. We used movement‐based kernel density estimation to identify migration corridors for each species. We overlaid these corridors on maps of the distribution and intensity of economic activities, quantified the extent of overlap and threat posed by each activity on each species, and compared the effects of activities. These results were compared with annual bycatch rates in the respective fisheries. Both species' 3 corridors overlapped most with longline fishing, but the effect was worse for leatherbacks: their bycatch rates of approximately 1500/year were substantial relative to the regional population size of <100 nesting females/annum. This bycatch rate is likely slowing population growth. Artisanal fisheries may be of greater concern for loggerheads than for leatherbacks, but the population appears to be withstanding the high bycatch rates because it is increasing exponentially. The hydrocarbon industry currently has a moderately low impact on both species, but mining in key areas (e.g., Southern Mozambique) may undermine >50 years of conservation, potentially affecting >80% of loggerheads, 33% of the (critically endangered) leatherbacks, and their nesting beaches. We support establishing blue economies (i.e., generating wealth from the ocean), but oceans need to be carefully zoned and responsibly managed in both space and time to achieve economic (resource extraction), ecological (conservation, maintenance of processes), and social (maintenance of alternative livelihood opportunities, alleviate poverty) objectives. Abstract : Article Impact statement : Generating wealth from the oceans requires careful zoning of activities to avoid intensifying threats to conservation‐dependent species.